Color-Dependent Motion Illusions in Stationary Images and Their Phenomenal Dimorphism. (September 2014) - Kitaoka, Akiyoshi
The color-dependent motion illusion in stationary images—a special type of the Fraser–Wilcox illusion—is introduced and discussed. The direction of illusory motion changes depending on whether the image is of high or low luminance and whether the room is bright or dark. This dimorphism of illusion was confirmed by surveys. It is suggested that two different spatial arrangements of color can produce the motion illusion. One is a spatial arrangement where long- and short-wavelength color regions sandwich a darker strip; the other is where the same color regions sandwich a brighter strip.